Diet Analysis on Sugar Consumption among a Sample of Iraqi Patients - Nidhal A Ali; Bushra Hamza
The aim of this study is to compare sugar consumption before and after the sanctiona forced on Iraq. The sample consisted of 250 patients (125 female and 125 male) at age (20-50) years attending dental clinic using diet analysis sheets designed according to the ones introduced in professor's Andlaw manual of Pedodontics with some modifications. Results showed that 70%, 25.2%, 4.8% of the sample had (40; 30-40; 15-30) Kg/person/year sugar consumption before sanctions which is reduced to (84.8%, 10%, 5.2%) with (15; 15-30; 40-45) Kg/person/year after sanctions but there isn't so much reduction in the frequency of sugar consumption 97, 4-6, 4-6), (4-7, 4-7, 7 times and over) before and after sanctions which reveal an expected fall in severity and incidence of dental caries.